'Bakulan Rt 36', web media for supporting women's economic empowerment in Yogyakarta. (2016) - Widyastuti, Dhyah Ayu Retno; Herawati, F. Anita; Wulandari, Theresia Diyah; Arifin, Pupung; Handarkho, Yonathan Dri
Women empowerment is one of the 2015 MDG goals. In the current digital era, all processes are eased by ICT usages. The World Bank in 2002-2009 reported that Indonesia has 87% total internet access population with a small number applied to supporting economic activities, including women. The study has been conducted at Kampung Cyber RT 36. It conducted deep analysis on PAR method on the participation of men and women as an integral part. The research programme is going to hold problem solving due to research subject needs (Mikkelsen, 2001), while gender perspectives is applied to solve the research problem. Diffusion innovation theory is chosen as the reality framework (Rogers, 1995). The result of our study shows that there is a way to develop women capacity. Based on need assessment of the target groups, the team held programmes such as training programme and build website prototype to promote their businesses. It created Bakulan RT 36%.